2022
DOI: 10.3389/fpsyt.2022.873953
|View full text |Cite
|
Sign up to set email alerts
|

How Impulsiveness Influences Obesity: The Mediating Effect of Resting-State Brain Activity in the dlPFC

Abstract: Impulsiveness is a stable personal characteristic that contributes to obesity and may interact with it. Specifically, obesity is caused by unrestrained impulse eating that is not consciously controlled and leads to a hormonal imbalance that also can impair impulse control. However, the mechanism of this relationship is unclear. In our study, 35 obese individuals (body mass index, BMI > 28) were recruited and matched with 31 healthy controls (BMI < 24) in age and education level. All the participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…On the other hand, we observed that the ELS in uenced anticorrelation of the right SMG seed with the somatosensory (left postcentral gyrus) and impulse control (left MFG) clusters was weaker in AUD-low BMI individuals compared to those with high BMI, which in light of previous ndings 27,28,[52][53][54] , suggest elevated impulsivity and poor self-control behaviors in AUD with co-occurrence of high BMI. The ndings suggest two potential scenarios: either ELS contributes to overeating in individuals with AUD, or ELSinduced overeating increases their susceptibility to excessive alcohol consumption.…”
Section: Discussionsupporting
confidence: 61%
“…On the other hand, we observed that the ELS in uenced anticorrelation of the right SMG seed with the somatosensory (left postcentral gyrus) and impulse control (left MFG) clusters was weaker in AUD-low BMI individuals compared to those with high BMI, which in light of previous ndings 27,28,[52][53][54] , suggest elevated impulsivity and poor self-control behaviors in AUD with co-occurrence of high BMI. The ndings suggest two potential scenarios: either ELS contributes to overeating in individuals with AUD, or ELSinduced overeating increases their susceptibility to excessive alcohol consumption.…”
Section: Discussionsupporting
confidence: 61%
“…sleep disorders, weight [42,67,86]), many health risks (e.g. substance misuse, self-harm, high risk sexual behaviour) are more likely to relate to the underlying neuropsychological processes in ADHD such as difficulties in evaluation of risk and delay discounting [87][88][89] and associations with impulsivity [90][91][92][93][94][95][96][97][98][99].…”
Section: Discussionmentioning
confidence: 99%
“…Impulsivity is a multi-faceted construct [ 104 ] whose features represent risk factors for obesity [ 67 ] and have been associated with unsuccessful outcomes of its treatment [ 74 , 75 , 77 ]. However, prefrontal cognitive control could also serve as a potential target for the treatment of obesity [ 105 ]. From a psycho-behavioural perspective, interventions designed for specific disorders, like ADHD or BED -characterized by high impulsive behaviours and lack of control- could also be useful for patients with obesity, even for those that do not necessarily present one of these psychological disorders.…”
Section: Discussionmentioning
confidence: 99%